2021
DOI: 10.1186/s13005-021-00284-0
|View full text |Cite
|
Sign up to set email alerts
|

A study on the association between accessory maxillary ostium and maxillary sinus mucosal thickening using cone beam computed tomography

Abstract: Background Accessory maxillary ostium (AMO) has a major role to play in the aetiology of maxillary sinusitis. Mucosal thickening is one of the key radiographic features of chronic maxillary sinusitis. The aim of this study was to identify the location of the AMOs and investigate the association between Mucosal Thickening [MT] and AMO using Cone Beam Computed Tomography [CBCT]. Methods CBCT scans of 400 maxillary sinuses from the records of 200 pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Although there is great variability in the data obtained by other authors, the results obtained in this work indicated a close concordance with some published data concerning antral septa [ 2 ], concha bullosa [ 2 , 28 , 45 ], Haller cells [ 2 , 32 , 36 ], accessory maxillary ostium [ 50 ], and uncinate process angulation [ 26 ]. Nonetheless, discordant data have also been reported regarding Haller cells [ 4 , 26 ] and the occurrence of accessory maxillary ostium [ 4 , 7 , 36 , 44 , 48 ]. It is important to point out here that the divergence between the outcomes might be attributable to factors related to anthropometric characteristics and the ethnic variability of the sample population, which may influence the anatomical configuration and location of these structures.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is great variability in the data obtained by other authors, the results obtained in this work indicated a close concordance with some published data concerning antral septa [ 2 ], concha bullosa [ 2 , 28 , 45 ], Haller cells [ 2 , 32 , 36 ], accessory maxillary ostium [ 50 ], and uncinate process angulation [ 26 ]. Nonetheless, discordant data have also been reported regarding Haller cells [ 4 , 26 ] and the occurrence of accessory maxillary ostium [ 4 , 7 , 36 , 44 , 48 ]. It is important to point out here that the divergence between the outcomes might be attributable to factors related to anthropometric characteristics and the ethnic variability of the sample population, which may influence the anatomical configuration and location of these structures.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the prevalence of accessory ostium was 35.5–56.7% [ 64 , 65 , 66 , 67 ]. Contrast to primary ostium, the accessory ostium was usually ovaloid (48.4%) or round (39.0%) instead of slit shaped (12.6%) [ 65 ].…”
Section: Anatomymentioning
confidence: 99%
“…Contrast to primary ostium, the accessory ostium was usually ovaloid (48.4%) or round (39.0%) instead of slit shaped (12.6%) [ 65 ]. The accessory ostium, if present, was on average 19.9 ± 1.7 mm from the most inferior point of the sinus floor [ 67 ]. The presence of sinusitis or mucosal thickening and accessory ostium were associated [ 66 , 67 ].…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…In a study investigating the incidence of accessory ostium in patients with chronic maxillary sinusitis, a close association of accessory ostium with chronic maxillary sinusitis was revealed [12]. According to Shetty et al [13], there was a clear association between the degree of mucosal thickening and the occurrence of AMO.…”
mentioning
confidence: 97%